CORONARY ARTERY CALCIFICATION IN LIVER TRANSPLANT RECIPIENTS - E.A. GRIGORENKO; N.P. MITKOVSKAYA; V.V. ROUDENOK; O.O. RUMMO (Avicenna Tajik State Medical University, 2020)
Objective: To study the dynamics of changes in the calcium index (CI) as a cardiovascular risk factor in patients with terminal liver diseases. Methods: A prospective, single-center cohort study included 250 patients who needed liver transplantation. The duration of the follow-up period was 5.4±3.29 years from the moment of their inclusion on the waiting list. In addition to the assessment of prevalence and dynamics of traditional cardiovascular risk factors, indicators of the CI were determined by the method of multispiral computed tomography at the time of patients' inclusion in the study and after 5 years of dynamic follow-up. Results: The CI in patients with terminal liver diseases requiring transplantation was found to exceed the limits of the recommended norm determined by the 75th percentile in 152 (56.3%) subjects at the stage of their inclusion on the waiting list. Comparison of coronary calcification after 5 years of dynamic observation in liver transplant recipients revealed higher values of the CI compared with those in patients with terminal liver diseases who did not receive a donor organ (CI, AJ-130 - 223 (38; 597) and 141 (4; 176) units respectively, p<0.05; CI, Volume-130 - 314 (73; 748) and 203 (8; 284) mm2 respectively, p<0.01) as well as in patients with metabolic syndrome (CI, AJ-130 - 186 (78; 463) and 74 (21; 192) units respectively, p<0.01; CI, Volume-130 - 278 (74; 623) and 124 (74 ; 273) mm2 respectively, p<0.01) and/or coronary artery disease (CI, AJ-130 - 274 (102; 683) and 109 (34; 246) units respectively, p<0.01; CI, Volume-130 - 382 (98; 834) and 382 (98; 834) mm2 respectively, p<0.01) in the general population. Conclusion: The results of the study indicate that in the long-term postoperative period, liver transplant recipients receiving immunosuppressive therapy, despite a radical solution to the problem of liver failure, developed coronary artery disease during five years of dynamic follow-up. In the study cohort, in the post-transplant period, there was an increase in the calcium index in comparison with the indicators obtained when patients were included in the waiting list, as well as in comparison with the value of the calcium index of patients with metabolic syndrome and coronary artery disease from the general population.